Primary Hydatid Cyst and Isolated from the Thigh: An Exceptional Localization (Archives of Clinical and Medical Case Reports, 2018)
Muscular involvement with Echinococcusgranulosus is rare, even in endemic countries where the frequency is estimated to be less than 3%, particularly in the countries of the Mediterranean basin, North Africa and Latin America. We report the rare observation of a hydatid cyst of the internal thigh room in a 57-year-old patient of rural origin and who has no notable sickness antecedents and was hospitalized in our department for the exploration of a tumefaction of the internal surface of the left thigh appeared gradually and insidiously for 3 years. Magnetic resonance imaging (MRI) showed an oval mass evoking an intramuscular hydatid cyst and its relationship to neighboring structures. He underwent surgical excision under locoregional anesthesia. Solitary hydatid localization in muscle tissue is exceptional, but it is useful to know that its diagnosis is often delayed, its treatment is surgical, but recurrences are possible.